Analisis Numerik Stabilitas Lereng Terhadap Curah Hujan Pada Tanah Tak Jenuh - Ramadhan, Rabbani Isya; Hamdany, Abdul Halim; Adiguna, Glenn Adriel; Satyanaga, Alfrendo (Institut Teknologi Bandung, 2024)
Abstract Unpredictable climate change makes high intensity rainfall infiltration possible in the future. This can cause slope collapse due to rainfall infiltration. Indonesia has areas that are very susceptible to slope collapse due to rainfall. The purpose of this study was to determine the characteristics of the pore water pressure distribution and slope stability during rainfall on the original slope through numerical modeling. The groundwater characteristic curve was measured using high-suction polymer sensors (HSPS). Volume changes in the soil were obtained using a 3D scanner. Numerical modeling was carried out with the help of GeoStudio. Seepage analysis was carried out using SEEP/W to obtain changes in the pore water pressure distribution due to rainfall infiltration. Slope stability was carried out using SLOPE/W to determine the slope safety factor due to rainwater infiltration. The results showed that the intensity and duration of rainfall had a significant effect on slope stability. The longer the duration of rainfall and with high intensity can cause a greater decrease in the safety factor. This is because the suction power of the soil has decreased and causes the shear strength of the soil to be lower so that it can cause slope failure. Keywords: Unsaturated soil, SWCC, rainfall infiltration, slope stability